DISKOMINFOTIK AND KPID WEST NUSA TENGGARA READINESS IN DIGITAL BROADCAST MIGRATION (ANALOG SWITCH OFF) - Najamudin; Halim, Sahril; Wahyudi, Gemuh Surya; Khan, Shabeer; Gina Salsabila, Nuria (Universitas Islam Negeri Mataram, 2024)
This research highlights the migration of analog TV to digital TV promoted since 2007 through the Decree of the Minister of Communication and Information (Diskominfotik) Number: 07/M.KOMINFO/3/2007. The push and pull to realize this big agenda in the broadcasting world is very strong. This study uses qualitative research. Diskominfotik through the Indonesian Broadcasting Commission (KPI) West Nusa Tenggara Region as the regulator is still in the wait-and-see stage. This is due to waiting and seeing any developments at the Diskominfotik and KPI at the central level. Although in subsequent developments, the Automatic Switch Off (ASO) will be implemented in August 2023 which will have an impact on local TV media in West Nusa Tenggara (NTB).